2017
DOI: 10.1073/pnas.1718592114
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of agonists of growth hormone-releasing hormone (GHRH) in early experimental diabetic retinopathy

Abstract: SignificanceThe studies described here are relevant to the cure of diabetic retinopathy, a leading cause of blindness with currently limited therapeutic options. Here we provided evidence showing that agonists of growth hormone-releasing hormone (GHRH) can significantly diminish retinal neurovascular injury characterizing the early stages of diabetic retinopathy through antioxidant and anti-inflammatory effects. The results of the presented studies provide information on the potential therapeutic effects of GH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 44 publications
5
33
0
1
Order By: Relevance
“…We finally evaluated the effects of MIA-690 ( www.nature.com/scientificreports www.nature.com/scientificreports/ Discussion GHRH and mRNAs for GHRH-R have been found in rat cortex and brain stem 22,23 , and various reports suggested that GHRH might play a key role in cognitive and mood disorders 20,[24][25][26][27][28] . GHRH-antagonists compounds can exert powerful antitumor effects, possibly related in part to their antinflammatory and antioxidant properties 17,[29][30][31][32][33] . In the present study we show that MIA-690, a GHRH antagonist, and MR-409, a GHRH analog, exhibit antinflammatory and antioxidant effects on prefrontal cortex specimens, ex vivo (Figs.…”
Section: Mr-409 Induced Down Regulation Of P Ghrh-r Gene and Protein mentioning
confidence: 99%
See 2 more Smart Citations
“…We finally evaluated the effects of MIA-690 ( www.nature.com/scientificreports www.nature.com/scientificreports/ Discussion GHRH and mRNAs for GHRH-R have been found in rat cortex and brain stem 22,23 , and various reports suggested that GHRH might play a key role in cognitive and mood disorders 20,[24][25][26][27][28] . GHRH-antagonists compounds can exert powerful antitumor effects, possibly related in part to their antinflammatory and antioxidant properties 17,[29][30][31][32][33] . In the present study we show that MIA-690, a GHRH antagonist, and MR-409, a GHRH analog, exhibit antinflammatory and antioxidant effects on prefrontal cortex specimens, ex vivo (Figs.…”
Section: Mr-409 Induced Down Regulation Of P Ghrh-r Gene and Protein mentioning
confidence: 99%
“…Accordingly, various studies showed that GHRH and GHRH antagonists can influence the inflammatory and reduction/oxidation (redox) status in cancer and other tissues 29,33 . www.nature.com/scientificreports www.nature.com/scientificreports/ In particular, MIA 690 decreased inflammation by reducing the infiltration of macrophages and leucocytes, the production of TNF-α, IL-1β, and monocyte chemotactic protein-1 (MCP-1) in tissue after insult with lipopolisaccaride (LPS) and the production of the pro-inflammatory markers in carrageenan-induced chronic prostatis 31,32 . In addition, MIA-690 showed antioxidant and neuroprotective properties 28 .…”
Section: Mr-409 Induced Down Regulation Of P Ghrh-r Gene and Protein mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, GHRH antagonist treatment has been shown to result in a significant alteration of the outer retinal layer and worsened retinal morphology. 17 Therefore, preserving cell survival may prevent NPDR progression. In this study, we report that cell apoptosis was decreased after the knockdown of Egr1, which suggests that the down-regulation of Egr1 may be an effective method to sustain HRVECs viability.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent images were taken at constant interval for every mouse studied in each experimental group. In addition, we assessed vascular permeability quantitatively by measuring albumin extravasation to the retinal tissue as described before [37]. Briefly, the mice were deeply anesthetized with ketamine/xylazine (80/12 mg/kg of body weight, respectively).…”
Section: Assessment Of Retinal Vascular Permeabilitymentioning
confidence: 99%